Analysis of pressure assisted incremental sheet forming process through simulation - Kumar Y.; Kumar S. (My University, 2025)
Incremental sheet forming (ISF) process is a flexible manufacturing process to produce complex 3D products at reasonable manufacturing cost. In addition to a single point, incremental sheet forming pressure has been applied to the back side of sheet surface in order to provide support to the sheet surface and improve process efficiency. In the current work, a comparative analysis of ISF & pressure assisted ISF process through CAE simulation have been done to predict the forming forces, energy requirements, effective stresses, etc. The forming forces in ISF as well as pressure-assisted ISF is very low when as compared to forming forces in traditional forming processes. The pressure-induced ductility has resulted in the reduction of forming forces with pressure assisted ISF. The energy required in pressure assisted ISF is slightly higher than the ISF process. An increment in effective stresses is observed in pressure assisted ISF, which is a due application of force on both sides of the sheet. However, these stresses are local and very small when as compared to traditional forming processes. © TJPRC Pvt. Ltd.